Survey of Trichogramma species associated with sugar cane in Colombia - GÓMEZ-L., LUIS ANTONIO; DÍAZ-M., ANA ELIZABETH; LASTRA-B., LUZ ADRIANA (Revista Colombiana de Entomología, 1996)
Diatraea spp. populations have been managed in some areas of the Cauca Valley, Colombia, by means of inundative releases of Trichogramma sp. However, recent field evaluations díd not reveal significant benefits resulting from these liberations. Comparative taxonomic studies confirmed that two species were involved: T pretiosum, the species reared and released commercially, and T exiguum, the species obtained fromDiatraea eggs collected in the field. Samples taken from different creas of the country showed that the only species found parasitizing Diatraea spp. eggs are T exiguum. Additional information about morphological characteristics is given to differentiate T atopovirilia and T. fuentesi, other species found in Colombia wad recorded in America as parasites of Diatraea spp. eggs. It is suggested that T exiguum should be mass-reared and released in commercial sugar cane fields to manage Diatraea spp. populations.